セールロンダーネ サンチ チガク セイブツ チョウサ タイ ホウコク 1988-89 (JARE-30) - 森脇, 喜一; モリワキ, キイチ; 船木, 實; フナキ, ミノル; 平川, 一臣; ヒラカワ, カズオミ; 時枝, 克安; トキエダ, カツヤス; 阿部, 博; アベ, ヒロシ; 東, 正剛; ヒガシ, セイゴ; et al. (1989)
P(論文) 第30次南極地域観測隊(JARE-30)夏隊のセールロンダーネ山地地学・生物学調査は, 1988年12月29日から1989年2月1日にかけて山地西部で, 2月2日から9日にかけてあすか観測拠点をベースに付近の小山塊で実施された。2月になってからの調査活動は, ブリザード等の強風と地吹雪で効率的でなかった。JARE-26-29の地学調査に生物班が初めて加わったが, 調査計画の立案や行動形態に特に従来と変わったところはない。ここでは, 設営面を含む行動の概要と調査の概略, 調査期間の山地近辺の気象と雪氷状況を報告する。調査の成果については別途, 各分野で詳しく報告される。 The summer party of the 30th Japanese Antarctic Research Expedition (JARE-30) carried out the geomorphological, paleomagnetic, geodetic, zoological and botanical field work in the western part of the Sør Rondane Mountains for 35 days from December 29,1988 to February 1,1989,and around Asuka Station for 8 days from February 2 to 9,1989. The field work in February was largely hampered by bad weather including blizzard. In addition to earth scientists who have been in charge of the field operation of the Sør Rondane Mountains since JARE-26 (1985), biologists joined the field party for the first time this season under the similar planning and operating scheme formerly adopted. This is the report describing the results of field operations including logistics, a summary of the field work, and some information on weather and surface conditions of snow and ice around the Mountains during this period. departmental bulletin paper